Addressing the Pandemic Training Deficiency: Filling the Void with Simulation in Facial Reconstruction. (3rd March 2021) - Yang, Shiayin F.; Powell, Allison; Srinivasan, Sudharsan; Kim, Jennifer C.; Baker, Shan R.; Green, Glenn E.; Zopf, David A.
Abstract : Objective/Hypothesis: To assess the use of a three‐dimensional (3D) printed, multilayer facial flap model for use in trainee education as an alternative method of teaching surgical techniques of facial reconstruction. Study Design: Cohort study. Methods: A 3D printed facial flap simulator was designed from a computed tomography scan and manufactured out of silicone for low‐cost, high‐fidelity simulation. This simulator was tested by a group of Otolaryngology–Head and Neck Surgery trainees at a single institution. The simulator group was compared to a control group who completed an exercise on a traditional paper facial flap exercise. Both groups underwent didactic lectures prior to completing their respective exercises. Pre‐ and post‐exercise Likert scale surveys measuring experience, understanding, effectiveness, and realism were completed by both groups. Central tendency, variability, and confidence intervals were measured to evaluate the outcomes. Results: Trainees completing the facial flap simulator reported a statistically significant (p < 0.05) improvement in overall expertise in facial flap procedures, design of facial flaps, and excision of standing cutaneous deformities. No statistically significant improvement was seen in the control group. Conclusions: Trainees found the facial flap simulator to be an effective and useful training tool with a high level of realism in surgical education of facial reconstruction. Surgical simulators can serve as an adjunct to trainee education, especially during extraordinary times such as the novel coronavirus disease 2019 pandemic, which significantly impacted surgical training. Level of Evidence: NA Laryngoscope, 131:E2444–E2448, 2021